2015
DOI: 10.3390/catal5031417
|View full text |Cite
|
Sign up to set email alerts
|

Photohydrogenation of Acetophenone Using Coumarin Dye-Sensitized Titanium Dioxide under Visible Light Irradiation

Abstract: Abstract:The use of coumarin dyes adsorbed on titanium dioxide (TiO2, P25) successfully extended the photocatalytic UV response of TiO2 toward visible light region. The hydrogenation of acetophenone (AP) using TiO2 modified with coumarin dyes proceeded with good chemical efficiencies under visible light irradiation. The role of sacrificial reagents on this dye-sensitized system is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Kohtani’s group has conducted a series of excellent work on TiO 2 photocatalytic transfer hydrogenations of aryl carbonyl compounds using alcohols as hydrogen donors [55,85,86,87,88,89,90]. In their most recent work, even moderate enantioselectivity for aryl ketones’ conversion to chiral secondary aryl alcohols was realized (as shown in Scheme 8) [56].…”
Section: Transfer Hydrogenation Of C=o and C=n Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohtani’s group has conducted a series of excellent work on TiO 2 photocatalytic transfer hydrogenations of aryl carbonyl compounds using alcohols as hydrogen donors [55,85,86,87,88,89,90]. In their most recent work, even moderate enantioselectivity for aryl ketones’ conversion to chiral secondary aryl alcohols was realized (as shown in Scheme 8) [56].…”
Section: Transfer Hydrogenation Of C=o and C=n Bondsmentioning
confidence: 99%
“…Furthermore, the efficiency of this visible-light-sensitized protocol was greatly increased by the introduction of more absorptive dyes. A series of pristine and thiophene-modified coumarin derivatives were chosen as the photosensitizers for visible-light driven TiO 2 photocatalytic transformation of acetophenone to 1-phenyl-ethanol [88]. The irradiation time to reach the same conversion was greatly shortened compared with the previous dye-sensitized system when appropriate hydrogen donor was chosen.…”
Section: Transfer Hydrogenation Of C=o and C=n Bondsmentioning
confidence: 99%
“…Adapted with permission from reference [72]. Kohtani et al also reported the photohydrogenation of AP derivatives on P25 TiO2, modified with metal-free organic dyes such as rhodamine B, fluorescein, and coumarin derivatives [77,78]. The use of these organic dyes successfully extended the UV response of TiO2 to the visible light region, though these reaction rates were much slower than the hydrogenation rate using UV excitation of Kohtani et al also reported the photohydrogenation of AP derivatives on P25 TiO2, modified with metal-free organic dyes such as rhodamine B, fluorescein, and coumarin derivatives [77,78].…”
Section: Hydrogenation Of Carbonyl Compoundsmentioning
confidence: 99%
“…The use of these organic dyes successfully extended the UV response of TiO2 to the visible light region, though these reaction rates were much slower than the hydrogenation rate using UV excitation of non-modified TiO2. In this dye-sensitized system, the electron injection from dye into TiO2 can take Kohtani et al also reported the photohydrogenation of AP derivatives on P25 TiO 2, modified with metal-free organic dyes such as rhodamine B, fluorescein, and coumarin derivatives [77,78]. The use of these organic dyes successfully extended the UV response of TiO 2 to the visible light region, though these reaction rates were much slower than the hydrogenation rate using UV excitation of non-modified TiO 2 .…”
Section: Hydrogenation Of Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation